Izinselelo ezibhekene nothisha abafundisa isiZulu njengolimi lokuqala lokwengeza ezikhungweni zemfundo ephakeme ezizimele eGoli: [English translation: The challenges facing by isiZulu lecturers teaching isiZulu in some private higher institutions in Gauteng] - Msomi, Melusi Ernest (Journal for Language Teaching, 2023)
This paper investigates the challenges facing by isiZulu lecturers in private institutions in Gauteng. These institutions train both foundation and intermediate student teachers who will teach in primary schools. This means that these students should be trained in all school subjects because they do not have major subjects like those who will teach in the senior and FET phase. The problem is that students who are training in these institutions are coming from all parts of South Africa and these higher institutions do not offer all African languages. They only have sePedi, seTswana and isiZulu. Xhosa, Ndebele and Swati students are forced to do isiZulu as a First Additional Language. These students have never studied isiZulu in their lives; this is their first encounter with it. They lack knowledge of isiZulu, as much as they can understand it spoken. They cannot write and read it. In this situation lecturers are expected to perform miracles in ensuring that these students learn isiZulu in a very short period of time. A qualitative approach has been used as a method of data collection in this paper. Interviews were conducted to gather data from participants. Language management theory has been used as theoretical framework for this paper. This theory looks at language planning at two levels, a macro-and a micro-planning level. The analysis found that non-Zulu students did not really like the Zulu language. They learned it because they were forced by circumstances. This paper recommends that the Department of Higher Education ensures that the use of indigenous languages is carried out effectively in higher education institutions, especially in the private sector. It is noteworthy that the teaching of indigenous languages in these institutions is neglected because even the teaching resources are inadequate. It turns out that it is the lecturers’ responsibility to plan what they will teach